Formulationg the Strategy for Agrotourism Destinations: Nglinggo Tourism Vilage, Samigaluh, Kulon Progo - Umi Murtini; Purnawan Hardiyanto (European Scientific Journal, ESJ, 2023)
This study aims to develop a strategy to attract tourists to visit Nglinggo tea plantation as a tourist destination in Samigaluh, Kulon Progo Regency. The research data used primary data, which was collected using interviews, filling out questionnaires and focus group discussions. The data were obtained from the tourists visiting Nglinggo tea plantation, the tour managers and Pager Harjo village officials. The analysis tools used the External Factor Evaluation Matrix (EFE), Internal Factor Evaluation Matrix (IFE) and the Quantitative Strategic Planning Matrix (QSPM). From the IFE and EFE matrices results, the SWOT table is compiled to obtain several alternative strategies. The alternative strategies are analyzed using QSPM to get the right strategy. The results of the analysis obtained IFE and EFE values above the average. The educational value of picking and processing tea and its culture had more excellent value than its weaknesses, namely the destruction by tourists and lack of roads and electricity infrastructures. The external environmental conditions that become the opportunities are the changes in people's lifestyles, the support from the government for tourism development and the outstanding image by tourists. The strategic options that can be taken are making the activity of drinking tea a tradition in Indonesia, increasing the educational tours of picking and processing tea, working with the government to build roads that facilitate the tourists to get to the tourist attractions safely and increasing the electrical installations around the tourist attractions as well as educating the public and the tourists about the conservation of the environment.